The mosaic tiled harvestmen—taxonomic review of Gonyleptellus Roewer, 1930 (Opiliones: Gonyleptidae: Gonyleptinae) - de Ázara, Ludson Neves; Kury, Adriano Brilhante (Zootaxa, 2019)
The genus Gonyleptellus Roewer, 1930 is revised and reordered; a new species Gonyleptellus angeloi sp. nov. is described from Nova Friburgo, Rio de Janeiro, three additional species are transferred from other genera and one species is removed, resulting in five species in this genus. The following nomenclatural acts are proposed herein: Gonyleptes pustulatus Sørensen, 1884 is transferred from Gonyleptes to Gonyleptellus; Gonyleptes cancellatus Roewer, 1917 and Progonyleptoides pustulosus Mello-Leitão, 1935, both currently under the synonymy of Gonyleptellus bimaculatus (Sørensen, 1884), are revalidated and transferred to Gonyleptellus. Stephanocranion bimaculatus Mello-Leitão, 1931, previously considered a junior synonym of Gonyleptes cancellatus Roewer, 1917, and thereby previously carried under the synonymy of Gonyleptes bimaculatus Sørensen, 1884, is here unlinked with the former but kept under the synonymy of the latter (of which it is also a junior secondary homonym). Stephanocranion serrulatum Mello-Leitão, 1940, currently under the synonymy of G. bimaculatus, is newly synonymized with P. pustulosus. Stephanocranion bufoninus Mello-Leitão, 1949 (currently combined under Gonyleptellus) is considered a junior subjective synonym of Discocyrtus crenulatus Roewer, 1913. The male of Gonyleptellus bimaculatus is described for the first time. The genus Gonyleptellus is restricted to the states of Rio de Janeiro and São Paulo, Brazil. A key and a map for all the five valid species are presented.